Transfusion Medicine and Scientific Developments - Koopman-van Gemert, A.W.M.M (IntechOpen, 2017)
Transfusion Medicine and Scientific Developments focuses on unknown aspects of blood cells and transfusion practice. Blood transfusion medicine has become a sophisticated and specialized field of medicine. Some aspects will be discussed in this book. The book has been divided into three sections. The first section includes chapters describing the immunological and coagulation-assisting functions of red blood cells and methods to measure their life span. The second section discusses the role of platelets in inflammatory processes. The third section reviews functional dose of RBC transfusions and transfusion practice in various clinical settings.